Factors influencing intrapatient variability of tacrolimus and its association with 1-year post-transplant outcomes in pediatric liver transplant recipients - Fang, Chuxuan; Dong, Chunqiang; Huang, Kaiyong; Wen, Ningyu; Chen, Yiyu; Tang, Shuangyi (Frontiers in Pharmacology, 2024)
Abstract Objective: To explore the factors influencing tacrolimus intrapatient variability (TAC-IPV) and its association with one-year post-transplant outcomes in pediatric liver transplant recipients. Methods: Clinical and biological data of pediatric patients after liver transplantation were collected. The patients were divided into high-IPV group and low-IPV group according to the median TAC-IPV for statistical comparisons. Factors which p<0.05 in univariate analysis were introduced into Binomial Logistic Regression Analysis. Correlation analysis was used to test the connections between the Tac-IPV and outcomes within 1 year after liver transplantation (LT). And Kaplan-Meier was used to drawn the survival curves. Results: A total of 116 children underwent 746 measurements of TAC trough concentrations. The median TAC-IPV was 32.31% (20.81%, 46.77%). Hematocrit (p=0.017) and concomitant medications (p=0.001) were identified as independent influencing factors for TAC-IPV. The incidence of transplant rejection (p=0.008), CMV infection (p<0.001), and hospital admission due to infection (p=0.003) were significantly higher in the high-IPV group compared to the low-IPV group. Kaplan-Meier survival analysis suggests that after considering the time factor, high IPV (IPV>32.31%) was still significantly associated with transplant rejection (HR=3.17, p=0.005) and CMV infection (HR=2.3, p<0.001) within 1 year after LT. Conclusion: The study highlights the significant variation in TAC-IPV among children post-liver transplantation, emphasizing the impact of hematocrit levels and concomitant medications on TAC-IPV. Elevated TAC-IPV is associated with increased risks of transplant rejection, CMV infection and readmission due to infection in the first year after liver transplantation. Close monitoring of patients with high TAC-IPV is recommended to promptly detect adverse reactions and provide timely intervention and treatment.